Design and Performance Analysis of Motor Drive System of Light Electric Vehicle - Shet, M. Satyendra Kumar; Revankar, Shripad T. (New Energy Exploitation and Application, 2025)
In this study, the development of vehicle dynamics models and analysis has been carried out for a light electric vehicle (LEV) based on a force model, torque, power‑speed profile, the driving cycle, and motor parameters. The proposed customized Electric Propulsion System (EPS) of the LEV consists of a unique 1.5 kW, 3‑phase, 4‑pole rectangular wave operation Permanent Magnet Brushless DC (PMBLDC) motor with a battery as an energy storage system, which is capable of running at speeds of about 30 km hr−1 up to 40 km hr−1 with a curb weight of 200 kg. Successfully integrating and optimizing the multidisciplinary subcomponents including Vehicle Body Structure (VBS), Electric Propulsion System (EPS), Energy Storage System (ESS), and Energy Management System (EMS) of the LEV system requires addressing challenges such as weight, safety, reliability, and cost while meeting the demands of diverse driving profiles and operational conditions. A simulation case study for the performance analysis of a 1.5 kW battery‑supported motor drive for the LEV has been carried out. Experiments have also been conducted on the performance of the permanent magnet brushless DC (PMBLDC) motor under different load conditions. From the case study, it has been found that the designed customized drive achieves maximum torque density with small torque pulsation through design optimization and a cost‑effective Proportional Integral (PI) Control technique. Furthermore, the drive eliminates input distortions and is characterized by low power consumption and high efficiency.